Endomyocardial biopsy in patients with cardiomyopathy of unknown origin: does specialized center experience apply to a tertiary care hospital?. (December 2016) - Tebbe, Ulrich; Bramlage, Karin; John, Fiete; Härtel, Dirk; Felgendreher, Ralf; Machalke, Kathrin; Kandolf, Reinhard; Bramlage, Peter
Abstract Background In patients with cardiomyopathy of unknown origin, endomyocardial biopsy provides the possibility of improved diagnosis and tailored treatment. Specific guidance has been developed based on cardiovascular centre of excellence experience but it is unknown if the benefits also extend into the tertiary care hospital setting. Methods Endomyocardial biopsies was performed in patients with cardiomyopathy of unknown origin. The outcomes were mirrored against the current ESC recommendations. Results A total of 57 patients with cardiomyopathy of unknown origin underwent endomyocardial biopsy with a mean age of 54 years and 28 % being women. In 17 patients (30 %), viruses were detected in the biopsy material, in 6 patients (11 %) cardiac amyloidosis was found of which 3 had also a positive test for viruses. The overall mortality rate was 18 % in the mean follow up period of 30 months, with a rate of 24 % in those with virus detection (mean FU 24 months) and 15 % in those without virus detection (mean FU 31 months. Death rates were 83 % in patients with cardiac amyloidosis (mean FU 10 months). Conclusion We conclude that, limited by uncertainty stemming from the small number of included patients, endomyocardial biopsy may not prove to have a clinical impact on treatment decisions and outcomes in a tertiary care hospital setting. We consider cardiac amyloidosis to be an exception, since the mortality rate with or without concomitant virus load was extremely high.